SCAPHOPODA (MOLLUSCA) OF FERNANDO DE NORONHA - PERNAMBUCO AND ATOL DAS ROCAS - RIO GRANDE DO NORTE, BRAZIL - Filho, Gilberto Faustino da Silva; Tenório, Deusinete de Oliveira; Pinto, Stefane de Lyra; Alves, Marcos Souto (Revista Nordestina de Zoologia, 2016)
It was studied the Scaphopoda from the National Marine Park of Fernando de Noronha (PARNAMAR-FN - PE) and from the Biological Reserve of Atol das Rocas - RN – Brazil. The material was collected in beaches of Fernando de Noronha, from 1990 to 2002, and in random collections in Atol das Rocas at a depth of 0-45 meters, from 1999 to 2002. The Dentaliidae with eight species: Dentalium laqueatum Verrill, 1885; Paradentalium americanum (Chenu, 1843); Paradentalium disparile (d'Orbigny, 1853); Paradentalium infractum (Odhner, 1931); Antalis antillaris (d'Orbigny, 1853); Graptacme calamus (Dall, 1889); Graptacme eborea (Conrad, 1846); Graptacme perlonga (Dall, 1881). The family Fustiaridae with Fustiaria liodon (Pilsbry & Sharp, 1897) and Gadilidae: Polyschides tetraschistus (Watson, 1879). The species, Dentalium laqueatum, Paradentalium americanum, Paradentalium disparile, Paradentalium infractum, Antalis antillaris, Graptacme calamus and Graptacme perlonga are cited for the first time to the Fernando de Noronha area. In Atol das Rocas it is recorded for the first time the occurrence of Graptacme perlonga, Fustiaria liodon and Polyschides tetraschistus, thus expanding the geographic distribution of these species in oceanic islands in Brazil.